PENDAMPINGAN ORANG TUA PADA ANAK SAAT BELAJAR DARI RUMAH DI PAUD MAITREYAWIRA PONTIANAK TENGGARA - Arniasih Sholehah; Aswandi Aswandi; Dian Miranda (Universitas Tanjungpura, 2022)
AbstractParental assistance when learning from home is an effort made by parents in providing the assistance needed by children while studying from home so that aspects of child development can develop optimally. This study aims to describe parental assistance to children when learning from home at PAUD Maitreyawira, Southeast Pontianak. The research method used is a descriptive method with a qualitative research form. The subjects in the study were the parents of children in class K1 Lucky PAUD Maitreyawira Southeast Pontianak. Data collection techniques used in this study were direct observation, direct communication, and documentary studies. The results of the study show that people have provided learning facilities that children need, supervise the use of children's study time, and supervise children's learning activities while studying from home. Thus, parental assistance to children when studying from home at PAUD Maitreyawira Southeast Pontianak has been carried out well.Keywords: Learning from Home and Parental Assistance